(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In the present paper, we apply the concept of reverse derivation in rings on the concept of d − algebra to obtain the concept called a left-right (resp. right-left) reverse derivations of d−algebra X (briefly, (l, r) resp. (r, l)− reverse derivation of d − algebra ), we will also, define some concepts such as regular map, composition two maps and study the related properties. Moreover, the notions of partial ordered edge d − algebra as well as d − subalgebra and their relation to our current study are obtained. In addition, some illustrative examples and counterexamples are discussed.